RELATIONSHIP BETWEEN BIOSECURITY PRINCIPLES AND CONSUMER ATTITUDES - Aila, Fredrick Onyango; Ochieng’, Isaac; Oima, David (European Scientific Journal, ESJ, 2013)
﻿﻿Indigenous chicken abound in Kenya and are produced under minimal/very low levels of biosecurity principles resulting in low productivity. Consumers however exhibit high preferences indigenous chicken products. The aim of this research was to establish the relationship biosecurity principles and intentions to consume indigenous chicken in Kisumu City, Kenya. The subaim was to test the significance of this relationship, if any. Using a descriptive research design, a questionnaire was administered on 281 respondents (females=48%) in Kisumu City (78% response rate), and relationship established through Spearman rank correlation. Observed low and insignificant correlations for management of the flock = .064 (p=.296); control ofincoming animals = .080 (p=.185); and control of other animals =.094 (p=120). Only control of in- and out-going materia l=.127 (p=.035) had a significant correlation with intention to consume. Concluded there is no significant relationship between biosecurity principles and intention to consume indigenous chicken. Thus, the puzzle linking biosecurity and preferences for indigenous chicken still exists given this evidence. The role of the government in providing information on biosecurity cannot be gainsaid as it creates impetus to demand high quality indigenous chicken products. Market mechanisms cannot fully reveal the underlying relationships between biosecurity principles and intention to consume indigenous chicken. Hence need for further research on a wider area utilizing non-market methods like contingent valuation and/or choice experiments to unlock these relationships.